81 PATIENT WITH COMPLICATED AORTIC DEFORMITIES IN ASSOCIATION WITH AN ATRIAL SEPTAL DEFECT AND INFECTIVE ENDOCARDITIS. (1st January 2005) - Mundo-Sagardia, J. A.; Johnson, C.; Calderon, R.; Quintana, C.
Abstract : Coarctation of aorta is strongly asssociated with bicuspid aortic valves. This is a risk factor for infective endocarditis. Aneurysm of a sinus of Valsalva is a rare defect with a prevalence of 0.09% and is associated in 10% of cases with bicuspid aortic valves and less frequently with coarctation of aorta and atrial septal defect. The association of coarctation of aorta with an atrial septal defect is rare. This is the first case reported in Puerto Rico of an adult patient with coarctation of aorta in association with a ruptured aneurysm of a sinus of Valsalva and an atrial septal defect. The patient is a 22 year old male with coarctation of aorta diagnosed since childhood, who was admitted at the Cardiovascular Center of Puerto Rico due to infective endocarditis secondary to teeth infection (caused by Streptococcus mitis) and signs of congestive heart failure. Upon evaluation with transthoracic and transesophageal echocardiograms, he was found to have coarctation of aorta in aortic isthmus, aortic root dilatation, bicuspid aortic valve with vegetation, severe aortic and tricuspid regurgitation, aneurysm of non coronary sinus of Valsalva with perforation to right atrium, biatrial enlargement and dilated right ventricle. Successful antibiotherapy of endocarditis was achieved. Afterwards, surgical replacement of aortic valve and ascending aorta and closure of non coronary sinus of Valsalva aneurysm was done. A secundum atrial septal defect was found and was also closed. Color photographic registration of the findings confirmed at surgery was obtained. Surgical correction of coarctation of aorta was postponed for a future time. The patient had a successful postsurgical recovery and was discharged home with anticoagulation treatment.